Optimasi Hardening Baja Karbon Sedang dengan Fluida Getah Pohon Pisang Menggunakan Metode Taguchi - Dimu, Roymons Jimmy; Widhiyanuriyawan, Denny; Sugiono, Sugiono (Jurnal Rekayasa Mesin, 2014)
The aim of this research is to increase the hardness of the material with hardening process. Factors that influence the hardening process are the raw material, the heating temperature, holding time and cooling medium. To obtain the optimum combination of factors hardening process, this research adopted the Taguchi experimental design method. The type used were orthogonal array L9 (34) which generates a combination of 4 factors with each factor has 3 levels.Raw materials used were retrieved from the leaf springs trucks, jeeps and minibuses which are medium carbon steels with different chemical compositions. Based on the heating temperature recommended for medium carbon steel hardening process is between 723 - 900ºC then the heating temperature used 723ºC, 800ºC, 850ºC. Whereas for the holding time that carbon steel is recommended for 5-10 minutes, then the holding time used were 5, 7.5, 10 min. For the cooling medium used in this research are banana tree sap fluid and also water and oil as a comparison. In this research presented the results of hardness test hardening process with a combination of treatments truck spring steel material, temperature 850ºC, 10 min holding time and cooling medium with banana tree sap fluid in order to get the highest hardness worth HRC 63.03. Based on the analysis of Taguchi method can be seen that the four factors the most influence on hardness of material is temperature, holding time, cooling medium, and the smallest is the material.Keywords: Hardening, Banana Tree Sap Fluid, Taguchi